Pengaruh Bauran Pemasaran Ritel Terhadap Kepuasan Pelanggan Di Toko Cabbeng Pompanua Kecamatan Ajangale Kabupaten Bone - Suharjum, Suharjum; Purwanto, Agus; Jusmita, Jusmita (-, 2025)
This research aims to determine the influence of the retail marketing mix on customer satisfaction at the Cabbeng Pompanua Shop, Ajangale District, Bone Regency.The research methods used in this research are Quantitative and Qualitative Methods. The number of samples in this research was 100 people, sampling was taken by giving written questions to consumers of the Pompanua Cabbeng Shop. The results of this research indicate that the Retail Marketing Mix variable has a significant effect on customer satisfaction at the Pompanua cabbeng shop, Ajangale sub-district, Bone district. From the results of simple linear regression analysis, it is known that the regression coefficient value of the marketing mix variable is 0.628, where the significant value is 0.000, which means that the Marketing Mix has an influence on Customer Satisfaction because the regression coefficient value exceeds the significance value. The results of this correlation analysis show the number 0.543, which means that Theresults of the T test analysis obtained a t value for the Retail Marketing Mix variable of 6.395 t table of 1.660 and the significance of the two variables was 0.000 0.05, which means that the Marketing Mix has a positive and significant influence on Customer Satisfaction.